2013
DOI: 10.1186/1939-4551-6-7
|View full text |Cite
|
Sign up to set email alerts
|

The most common aeroallergens in a tropical region in Southwestern Iran

Abstract: BackgroundRespiratory allergies are the most important public health issues in the world. They are caused by aeroallergens which play great role in pathogenesis of respiratory allergic diseases.MethodsThe current study was conducted to evaluate the prevalence of positive skin test for various aeroallergens among allergic patients in Ahvaz, southwest Iran. 299 participants with allergic rhinitis (seasonal or perennial) were selected. Skin prick test using twenty three common allergen extracts was performed on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
36
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 32 publications
(66 reference statements)
7
36
1
4
Order By: Relevance
“…In recent years, the pollen of Acacia species such as A. farnesiana has been recognised as a cause of respiratory allergy in various parts of the Southern hemisphere [1, 4, 6, 7, 27–31]. Up to now, only one allergen (Aca f 2) of Acacia pollen has ever been identified as a member of the profilin family [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the pollen of Acacia species such as A. farnesiana has been recognised as a cause of respiratory allergy in various parts of the Southern hemisphere [1, 4, 6, 7, 27–31]. Up to now, only one allergen (Aca f 2) of Acacia pollen has ever been identified as a member of the profilin family [8].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, only one allergen (Aca f 2) of Acacia pollen has ever been identified as a member of the profilin family [8]. In this study a cDNA encoding another major allergen from Acacia pollen has been cloned, expressed, and identified as a member of the Ole e 1-like protein family, and its importance has been analysed with a population of patients living Ahvaz city, Southwest Iran, a tropical region in which Acacia pollen induces nearly 48% of the total sensitisation of patients with allergic rhinitis [4]. This allergenic member of the Ole e 1-like protein family of A. farnesiana was named Aca f 1 in accordance with the International Union of Immunological Societies (IUIS) Allergen Nomenclature Subcommittee (http://www.allergen.org/).…”
Section: Discussionmentioning
confidence: 99%
“…13 Many studies from hot and humid regions reported a high prevalence of mites allergy such as in Singapore, Malaysia and Thailand. [14][15][16] Similar conditions are found in Jeddah city with high prevalence of mites reactivity according to the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Iran, Prosopis juliflora pollen was the most common sensitizing tree pollen followed by pollen of Fraxinus americana tree. 13 Type of allergen pollen seemed to be dependent on the geographical and ecological distributions of trees.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported on the aeroallergen sensitivity of Iranian patients with asthma or rhinitis [5-7,32], and they found different prevalence rates among atopic subjects and different percentages of allergen sensitization. However, all of these studies agree that pollen sensitization is the most prevalent and that Chenopodiaceae, grass and sycamore are the most important allergenic sources.…”
Section: Discussionmentioning
confidence: 99%